2019
DOI: 10.1186/s40246-019-0209-3
|View full text |Cite
|
Sign up to set email alerts
|

IFITM5 pathogenic variant causes osteogenesis imperfecta V with various phenotype severity in Ukrainian and Vietnamese patients

Abstract: Background Osteogenesis imperfecta (OI) covers a spectrum of bone fragility disorders. OI is classified into five types; however, the genetic causes of OI might hide in pathogenic variants of 20 different genes. Often clinical OI types mimic each other. This sometimes makes it impossible to identify the OI type clinically, which can be a risk for patients. Up to 90% of OI types I–IV are caused by pathogenic variants in the COL1A1/2 genes. OI type V is caused by the c.-14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Other studies in the literature confirm this is a common clinical finding [37][38][39]. Other common clinical findings that might point to OI as a diagnosis include teeth brittleness, bluish sclera, hearing loss, long bone deformities, and joint laxity [37].…”
Section: Genetic Risk Factors and Heritable Diseasementioning
confidence: 60%
See 1 more Smart Citation
“…Other studies in the literature confirm this is a common clinical finding [37][38][39]. Other common clinical findings that might point to OI as a diagnosis include teeth brittleness, bluish sclera, hearing loss, long bone deformities, and joint laxity [37].…”
Section: Genetic Risk Factors and Heritable Diseasementioning
confidence: 60%
“…Clinical symptoms may once again vary widely but in a study of 13 patients with a molecularly confirmed mutation in the IFITM5 gene, 12 presented with interosseus radioulnar membrane ossification of the proximal forearm [36]. Other studies in the literature confirm this is a common clinical finding [37][38][39]. Other common clinical findings that might point to OI as a diagnosis include teeth brittleness, bluish sclera, hearing loss, long bone deformities, and joint laxity [37].…”
Section: Genetic Risk Factors and Heritable Diseasementioning
confidence: 99%
“…Type III and Type IV OI are moderately severe forms of the condition with variable phenotype in terms of the fracture history and stature. Type V OI is classified by the presence of interosseous membrane calcification, which results in limited supination and pronation (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…OI is a genetic condition, with most patients being affected by variants in genes known to be involved in the production or processing of type 1 collagen (1,5). The genes most commonly associated with this are COL1A1 and COL1A2, which follows an autosomal dominant (AD) pattern of inheritance (1,4,5). Over time, the number of genes recognised as part of OI has increased, including autosomal recessive variants (2,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation